ASSESSMENT OF GROUNDWATER QUALITY NEAR HOSPITAL WASTE TREATMENT PLANT - Adegbe, Elijah A.; Maina, R. L.; Okoro, P. N.; Jada, M. B. (FUDMA JOURNAL OF SCIENCES, 2023)
The study conducted a comprehensive assessment of the quality of selected groundwater sources around the liquid waste treatment plant of Ahmadu University Teaching Hospital Shika, Nigeria. Water samples were collected from four (4) hand-dug wells following standard procedures, ten (10) physicochemical parameters, and seven (7) heavy metals were analyzed. All the physicochemical parameters studied were within the WHO-specified limits except for D.O., which was less, and turbidity, which was higher. Heavy metals were found in all groundwater sources that were studied. However, the concentration of some heavy metals exceeded the specified limits recommended by the World Health Organization (WHO). The heavy metal presence in the groundwater sources may be connected to human activities such as waste disposal containing these metals around the groundwater sources and liquid waste from the hospital, which may have seeped into the wells. By implication, this study shows that the hand-dug wells were not safe for drinking. It is recommended that wells be sited away from dumpsites and waste treatment plants. Effluents from waste treatment plants should also be appropriately treated before their subsequent discharge into the environment. This study has generated baseline data that will be useful in monitoring heavy metal pollution
Keywords: Groundwater; Heavy metals; Physicochemical parameters; Lead; Iron